Mining industry association at multiple levels of governance drilling down - Kellow, Aynsley (Cambridge Scholars Publisher, 2022)
Many books on interest groups study how they conduct themselves in politics, and rather take for granted their existence. Unusually, this book examines the reasons why, for many years, there was no global level group representing the mining and non-ferrous metals industry and how the sector found a basis for association at the turn of the millennium, in response to the globalisation of environmental policy and the emerging focus on sustainable development. The associated reconfiguration of compétences at the national and state levels in Australia is also shown to have had important consequence.